2014
DOI: 10.1039/c4ay00817k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in electrochemical detection of arsenic in drinking and ground waters

Abstract: Anodic stripping voltammetry (ASV) using noble electrodes is based on the reduction of As3+ to As0, followed by its stripping or oxidation to As3+ or As5+ species, the two predominant forms of arsenic in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 91 publications
0
47
0
Order By: Relevance
“…It should be noted that in this paper we were most interested in the relative performance of the surfaces under study, and constant conditions were more important than maximising the sensitivity, which could have been done with longer deposition times at low As (III) concentrations to more accurately determine the practical LOD. There are many reviews that compare the sensitivity of surfaces for electrochemical determination of As(III), 12,57 and although direct comparisons of sensitivities are difficult due to different conditions used papers, the work presented here sheds further light on the reasons for differences amongst Au based surfaces. The precise reason for the improved sensitivity is difficult to determine, and may require further mechanistic studies, however there are some clues from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in this paper we were most interested in the relative performance of the surfaces under study, and constant conditions were more important than maximising the sensitivity, which could have been done with longer deposition times at low As (III) concentrations to more accurately determine the practical LOD. There are many reviews that compare the sensitivity of surfaces for electrochemical determination of As(III), 12,57 and although direct comparisons of sensitivities are difficult due to different conditions used papers, the work presented here sheds further light on the reasons for differences amongst Au based surfaces. The precise reason for the improved sensitivity is difficult to determine, and may require further mechanistic studies, however there are some clues from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, they rarely mention electrode lifetime, robustness (although this was done in [105,106]), surface renewal methods, or ease of manufacturing, all of which are essential for speciation analysis in the field. This may well explain why we found that there are relatively few examples of electrochemical analyzers suitable for on-site analysis in the literature [21,36,96,[107][108][109][110][111][112].…”
Section: As(iii) Determination By Anodic Stripping Voltammetry (Asv)mentioning
confidence: 98%
“…The various electrochemical techniques (voltammetry [9][10][11] and potentiometry [19], flow and amperometric methods), modes, and As speciation conditions [10], applied electrodes [10,11], electrode materials and their modification [11,18,21], biosensors [11,22], background electrolytes [19] as well as the measurement of parameters such as the limit of detection (LOD), linear range and sensitivity are summarized in reviews [9][10][11]. M A N U S C R I P T ACCEPTED MANUSCRIPT 2 The articles by Melamed and Yogarajah et al describe the test kits available for As determination and the characteristics of an ideal, routine arsenic sensor for field analysis combined with a microfluidic system for on-line monitoring of As levels [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Determinations were usually carried out using acidic solutions, however, in some procedures neutral [15,20], weak alkaline [24] and alkaline [23] supporting electrolytes were used. Several reviews were also reported on the measurement of arsenic by electrochemical stripping methods in natural waters and food samples [1,2,[29][30][31][32]. The main drawback of electrochemical stripping procedures is the presence of interference caused by other metal ions, especially copper, and natural organic compounds present in real samples.…”
Section: Introductionmentioning
confidence: 98%
“…They enter natural waters from natural earth deposits or from industrial and agricultural pollution. Arsenic contamination of drinking and ground waters affects more than 140 million people in 70 different countries on all six inhabited continents [2]. Taking into account different toxicity of inorganic arsenic forms new methods are needed that would enable speciation of arsenic to assess toxicity of water and other environmental samples.…”
Section: Introductionmentioning
confidence: 99%